Digital technologies in the prevention of diabetic foot: a review on mobile applications (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: Analyze mobile applications developed for prevention of diabetic foot.Method: Integrative review, with searches in LILACS, BDENF, Scopus, Web of Science and PubMed databases, from 2000 to 2019. After eligibility criteria, the sample consisted of nine articles. Results:The mobile applications for prevention of diabetic foot are based on online foot monitoring through images, evaluation of thermal images of the feet, capture of images of the sole of the foot, recommendations for self-care with the feet and classification of the risk of diabetic foot. The analysis of the articles shows that the applications were considered a good preventionstrategy. Conclusion:This study enabled the identification of nine mobile applications developed for prevention of diabetic foot, with predominance in the use of thermometry as the main measure for prevention and early detection of diabetic foot ulcers, with the use of thermal images and sensors associated with the mobile application.